Effects of the fixed oil of Butia catarinensis Noblick & Lorenzi on the erythrocyte membrane and bacterial strains (Research, Society and Development, 2022)
Butia catarinensis Noblick & Lorenzi, popularly known as “beach butiá”, is a species extensively used in the food area, but little explored regarding its toxicological safety and pharmacological potential. Therefore, the aim of this study was to evaluate whether the fixed oil of B. catarinensis (OFBc) promotes hemolysis in vitro and if it can increase the resistance of human erythrocytes to hemolysis (anti-hemolytic activity), and also to investigate whether it has antibacterial properties. The hemolytic, antihemolytic and antibacterial activities were described for the first time, respectively. For the study, human erythrocytes from healthy volunteers were isolated and incubated with different concentrations of the oil and Triton X-100 or 0, 24% NaCl as hemolysis inducers. OFBc showed low dose-dependent cytotoxicity to human erythrocytes. None of the concentrations exhibited cytoprotective effect nor inhibitory activity against the bacteria tested. In conclusion, the cytotoxicity screening performed in this study using the in vitro hemolysis assay suggests that the fixed oil of B. catarinensis may be pharmacologically safe for use in humans.